Toxicоlogical evaluation of the plant products using Brine Shrimp (Artemia salina L.) model - Меntor R. Hamidi; Blagica Jovanova; Таtјаnа Kadifkova Panovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2014)
Many natural products could serve as the starting point in the development of modern medicines because of their numerous biological and pharmacological activities. However, some of them are known to carry toxicological properties as well. In order to achieve a safe treatment with plant products, numerous research studies have recently been focused on both pharmacology and toxicity of medicinal plants. Moreover, these studies employed efforts for alternative biological assays. Brine Shrimp Lethality Assay is the most convenient system for monitoring biological activities of various plant species. This method is very useful for preliminary assessment of toxicity of the plant extracts. Rapidness, simplicity and low requirements are several advantages of this assay. However, several conditions need to be completed, especially in the means of standardized experimental conditions (temperature, pH of the medium, salinity, aeration and light). The toxicity of herbal extracts using this assay has been determined in a concentration range of 10, 100 and 1000 µg/ml of the examined herbal extract. Most toxicity studies which use the Brine Shrimp Lethality Assay determine the toxicity after 24 hours of exposure to the tested sample. The median lethal concentration (LC50) of the test samples is obtained by a plot of percentage of the dead shrimps against the logarithm of the sample concentration. LC50 values are estimated using a probit regression analysis and compared with either Meyer's or Clarkson's toxicity criteria. Furthermore, the positive correlation between Meyer's toxicity scale for Artemia salina and Gosselin, Smith and Hodge's toxicity scale for higher animal models confirmed that the Brine Shrimp Lethality Assay is an excellent predictive tool for the toxic potential of plant extracts in humans.